PERAN COMMISSION OF TRUTH AND FRIENDSHIP DALAM NORMALISASI HUBUNGAN BILATERAL INDONESIA – REPUBLIK DEMOKRATIK TIMOR LESTE - Abdi Nelson Simatupang; Faisal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This thesis is an international relations research in diplomacy studies study to describes the role of Commission of Truth and Friendship in normalizing bilateral relations between Indonesia and the Republic Demoratic Timor Leste. Commission was used as a facilitator to establish conclusive truths relating to events before and after the 1999 ballot and to promote reconciliation and friendship and ensure similar things did not happen in the future.This thesis used a pluralist perspective that views international relation not limited to relations between countries, but also relationships between individuals where the state is not always the main actor. This thesis hypothesis using the international organizational analysis level. In case the author used clive archer theory that the purpose of international organizations as arena can create prosperity through cooperation and collective action.The commssion of truth and friendship was formed from the agreement of Indonesia and the democratic republic of timor leste to find out the facts of human rights abuses throughout the history of east timor disintegration As well as reconciliation efforts that prioritize national interests through collective action to achieve common goals.Key Words: Role, Commission Of Truth and Friendship, Normalization, Indonesia, Republic Demokratic Timor Leste